Recent advances in microwave-assisted dry reforming of methane: catalyst, performance, and fundamentals - Kuang, Siyu (Frontiers in Chemistry, 2025)
The dry reforming of methane converts methane and carbon dioxide into syngas (a mixture of H2 and CO), which can be utilized for synthesizing downstream chemical products. However, its high endothermicity necessitates elevated operating temperatures (∼900 °C), posing challenges in energy efficiency and catalyst stability. Microwave-assisted heating has emerged as a promising alternative to conventional thermal catalysis, offering potential for enhanced reaction rates, improved energy utilization, and catalyst reactivation. This review systematically examines the recent advancements in microwave-assisted dry reforming of methane. It begins with an analysis of the reaction thermodynamics and fundamentals of microwave heating, specifically addressing its mechanisms and advantages over conventional methods. The core of the review focuses on the rational design of catalysts tailored for effective microwave absorption and catalytic performance. A critical comparison of catalyst performance under microwave versus conventional heating is provided, highlighting the roles of microwave in boosting conversion, suppressing coke deposition, and enhancing catalyst longevity. Finally, the review discusses the persistent challenges in scaling this technology and proposes future research directions, particularly in catalyst and reactor design and process intensification. This work underscores the transformative potential of microwave catalysis to drive efficient and sustainable dry reforming of methane processes.